Comparative Analysis of Construction Costs for Conventional and Precast Concrete in the Construction of a Laboratory Building at the State Islamic University of Tulung Agung, East Java - Mahendra, Bobby; Fadhilah, Qalya; Anwar, Saihul (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to quantitatively compare the cost and time efficiency between conventional concrete and precast concrete construction methods in the construction of the UIN Tulungagung Laboratory Building. The main focus of this study is to identify the most optimal method in the context of project implementation efficiency for medium-rise buildings in non-metropolitan areas. Scientifically, this study contributes to enriching the literature on the selection of construction methods based on location and project characteristics. Practically, the results of this study are expected to serve as a strategic reference for contractors, project planners, and other stakeholders in determining efficient construction methods that are appropriate for resource constraints, including budget, time, and equipment availability.